PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL BERBANTUAN WORKSHEET MATERI BANGUN RUANG SISI DATAR - Elsya Suharnita; Armis Armis; Rini Dian Anggraini (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2021)
This study aims to produce a digital learning media assisted by a flat-shape solid figures worksheet for 8th grade of SMP/MTs students that is valid and practical. The development model used in this study is the ADDIE model which consists of five stages, namely, analysis, design, development, implementation, and evaluation stages. Data collection techniques using validation sheets and student response questionnaires. The learning media validity test was carried out by three expert validators. There are 2 aspects of the assessment, namely the material aspect consisting of curriculum and learning, and the media aspect consisting of the program, media display, and worksheet display. The practicality test of learning media was carried out through a limited trial to 6 students. The results showed that the media validity test was in the very valid category. Furthermore, the results of the practicality test are in the very practical category. The conclusion of this study is that the worksheet-assisted digital learning media is very valid and practical to use in learning the material for flat-sided geometry.